The Role of Family Education in Heritage of Local Language Use: A Case Study of Families Associated with Javanese Transmigrant - Jeny Mardiyah; Alim Harun Pamungkas (Universitas Negeri Padang, 2021)
This research is motivated by the residents of Nagari Sungai Rumbai who are domiciled by several ethnic tribes such as Minangkabau, Javanese, Sundanese, and Batak residents. This heterogeneous tribe combines the original culture of each ethnic group living in Nagari Sungai Rumbai. This study aims to determine family education for the Javanese community in the habituation of the regional/(Javanese) language in the family, especially describing the role of family education at home, the role of family education in terms of the use of regional/(Javanese) languages, and knowing the supporting factors and inhibiting factors for the use of regional language/(Javanese). This type of research uses qualitative research methods using a case study approach. According to Creswell (2010), qualitative research always has its own characteristics. In another sense, qualitative research is a research approach that is carried out in a natural setting, placing the researcher as a data collection instrument, using inductive analysis and focusing on meaning according to the participant's perspective. Sources of data in this study that became the subject of the study were parents of families associated with Javanese transmigrant families in Nagari Sungai Rumbai, Dharmasraya Regency. While the informants are those who provide information about the research being carried out, namely, children or other family members in Javanese families. Data collection techniques used in this study were observation, interviews, and documentation. As well as the validity of the data obtained from this study was done by triangulation of sources. The results of the study show that (1) the role of family education at home is in the form of compassion (rasa), sharpening (cipta), and fostering (karsa), (2) the role of family education in terms of the use of regional languages, including families who have succeeded in teaching speech, namely passing on good use of the Javanese language to families and teach polite and courteous behavior, (3) the supporting factors are inviting to speak Javanese, marrying fellow Javanese descendants, and inviting children in social activities using the Javanese language. While the inhibiting factors are the influence of the majority language in which the regional language is used, the influence of the environment and association, and the younger generation does not appreciate the local language.